STRATEGI PENANGANAN KAWASAN PERMUKIMAN KUMUH OLEH DINAS PERUMAHAN, KAWASAN PERMUKIMAN DAN PERTANAHAN KOTA BEKASI (Studi Kasus pada Kelurahan Medan Satria) - Nabilah Az Zahra; Eka Yulyana (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
The emergence of slum settlements in Bekasi City is caused by the rapiddevelopment of the city and high urbanization, which causes population density to Housing, Settlement Areas and Land, is committed to overcoming this problem andimproving the conditions of these settlements. The aim of this research is todetermine the strategy for handling slum areas by the Bekasi City Housing,Settlement and Land Services Department. This research adopts the StrategyTheory proposed by Geoff Mulgan (2009) which includes goals, environment,direction, action and learning. The method used is a qualitative research methodwith data collection techniques using interviews, direct observation, documentationand physical devices. The research results show that the Department of Housing,Settlement Areas and Land is committed to creating slum-free areas by 2030through various activities such as building environmental roads, repairing canals,providing clean water facilities, building septic tanks, and providing rutilahuassistance. This research also shows that the Department of Housing, SettlementAreas and Land has succeeded in taking into account external and internal factorsin handling slum settlements, including challenges such as limited resources andcoordination between related parties. These obstacles were successfully overcomethrough synergy with various institutions involved in the program. Keywords: Strategy, Management of Slum Settlements, Housing Department, Settlement Areas and Land